A Detailed Optimisation of Solar Photovoltaic/Thermal Systems and its Application. (February 2019) - Antony, Anu; Wang, Y.D.; Roskilly, A.P.
Abstract: There have been various studies and experimental results analysing the operational behaviour of PVT, most of which has been done at steady state or quasi-state. Variable factors can be controlled to optimise the PVT output such as mass flow rate, irradiation falling on the PVT through tracking or incidence angles in a day and fixed factors that depend on the design of the chosen PVT system as well as location parameters such as ambient temperature, wind speed, Transport Fluid used, Difference in Structure, Packing Density, Nominal operating temperature, stagnation temperatures, Fill Factor, Thickness of each layer, Location and Latitude and Heat removal factor (harp or serpentine design). The aim of this research is to validate and predict the dynamic behaviour of PVT systems while accurately describing the factor responsible for the loss of efficiency at any point in time under various weather constraints. A commercial system was considered (Solar Angel PVT system) here and is simulated for an entire year. The system was modelled in MATLAB and solved in implicit RK-4 method. The research question finds out to establish the basis for a standard testing protocol for assessing PV-T performance throughout various differences. It also analyses the long-term dynamic performance of PV/T technology by providing evidential data analysis (solar irradiance, heat and electricity, ambient temperature, operational temperatures, flow rates and thermal storage capacity) while completing an assessment of PVT behaviour with respect to an equivalent PV under different weather conditions. The flow rates, heat removal factor and the location affect the thermal behaviour of the PV/T to a greater extent than nominal temperatures and stagnation temperatures.